Lycopene Potentiates the Protective Effect of Aliskiren on Doxorubicin-Induced Cardiomyopathy in Rats - Vinay Kumar; Surama Chauhan; K. Nagarajan; Bhulan Kumar Singh (Journal of Pharmacy and Nutrition Sciences, 2015)
Objective: The present study was designed to explore the combination therapy of lycopene with aliskiren in doxorubicin induced cardiomyopathy. Methods: Cardiomyopathy was induced in Wistar rats by i.p. administration of Doxorubicin (DOX) (15 mg/kg, single dose). Haemodynamic parameters (Systolic, diastolic blood pressure, Heart rate), heart weight, heart weight/body weight ratio, serum lactate dehydrogenase (LDH), oxidative stress (TBARS) and antioxidant enzymes (Glutathione, SOD and catalase) as well as transmission electron microscopein heart tissue were carried out. Results: There was significant increase in blood pressure, serum, lactate dehydrogenase (LDH), oxidative stress (TBARS) and significant decrease in heart weight, heart weight/body weight ratio and antioxidant enzymes in cardiomyopathic rats. Combined therapy of lycopene (2 and 4mg/kg) with aliskiren (100 mg/kg) treatment showed pronounced beneficial effecton above parameters.Furthermore lycopene with aliskiren significantly improves the antioxidant defense by increasing reduced glutathione, SOD, catalase, heart size and heart weight/body weight ratio. It is clearly observed from Transmission electron microscopic slides of DOX treated rats, there was swelling of mitochondria with disruption of cristae, rupture of nuclear membrane, condensation and margination of nuclear chromatins which were well protected by lycopene along with aliskiren treatment. Conclusion: Therefore, combination therapy of lycopene with aliskiren offers better treatment for DOX-induced cardiomyopathy than ALK alone.